Amelioration of diastolic dysfunction by dapagliflozin in a non-diabetic model involves coronary endothelium. (July 2020) - Cappetta, Donato; De Angelis, Antonella; Ciuffreda, Loreta Pia; Coppini, Raffaele; Cozzolino, Anna; Miccichè, Agostino; Dell'Aversana, Carmela; D'Amario, Domenico; Cianflone, Eleonora; Scavone, Cristina; Santini, Lorenzo; Palandri, Chiara; et al.
Graphical abstract: Abstract: The results of trials with sodium-glucose cotransporter 2 (SGLT2) inhibitors raised the possibility that this class of drugs provides cardiovascular benefits independently from their anti-diabetic effects, although the mechanisms are unknown. Therefore, we tested the effects of SGLT2 inhibitor dapagliflozin on the progression of experimental heart disease in a non-diabetic model of heart failure with preserved ejection fraction. Dahl salt-sensitive rats were fed a high-salt diet to induce hypertension and diastolic dysfunction and were then treated with dapagliflozin for six weeks. Dapagliflozin ameliorated diastolic function as documented by echo-Doppler and heart catheterization, while blood pressure remained markedly elevated. Chronic in vivo treatment with dapagliflozin reduced diastolic Ca 2+ and Na + overload and increased Ca 2+ transient amplitude in ventricular cardiomyocytes, although no direct action of dapagliflozin on isolated cardiomyocytes was observed. Dapagliflozin reversed endothelial activation and endothelial nitric oxide synthase deficit, with reduced cardiac inflammation and consequent attenuation of pro-fibrotic signaling. The potential involvement of coronary endothelium was supported by the endothelial upregulation of Na + /H + exchanger 1 in vivo and direct effects on dapagliflozin on the activity of this exchanger in endothelial cells in vitro . In conclusions, several mechanisms may cumulatively play a significant role in the dapagliflozin-associated cardioprotection. Dapagliflozin ameliorates diastolic function and exerts a positive effect on the myocardium, possibly targeting coronary endothelium. The lower degree of endothelial dysfunction, inflammation and fibrosis translate into improved myocardial performance.